Edukasi Kesehatan Melalui Media Booklet Dan Video Terhadap Tingkat Pengetahuan Remaja Putri Tentang Deteksi Dini Kanker Payudara - Kristine Dareda; Nurlela Hi. Baco; Sri Wahyuni; Mahrani Lakoro (Barongko: Jurnal Ilmu Kesehatan, 2026)
Knowledge can make young women understand more about the importance of conducting breast self-examination as an effort to determine the presence or absence of lumps that can develop into cancer in the breast. The purpose of this study was to determine the effect of health education through booklet and video media on the level of knowledge of adolescent girls about early detection of breast cancer at SMA Negeri 4 Kota Manado. The research design used was Two group pretest-postest. The sample in this study were 32 respondents with purposive sampling technique. The results of the study based on the Paired T-test which is seen at the final point of this test the ρ value in both experimental groups is both worth 0.000. The conclusion of this study is that there is an effect of health education through booklet and video media on the level of knowledge of adolescent girls about early detection of breast cancer at SMA Negeri 4 Kota Manado. The suggestion of this study is that young women are advised to carry out early detection of breast cancer by doing SADARI regularly.